Entre a posse e o uso: o processo de objetificação e comodificação de moças universitárias - Barbosa, Aline dos Santos (2019)
The choice between possession or use provides an opportunity to understand how liquid consumption can influence the process of turning humans into objects and possessions of another person. In this study, in-depth interviews with young female university students who experienced male abuse, document analysis and song lyrics helped to understand the commodification’s process under the light of solid and liquid consumption approaches. The results revealed that there are contexts of abuse in which boys opted for access to the body, sexuality, feelings and morality of the girls, permanently and maintaining a sense of ownership, characteristic of solid consumption, but also, opted for access to their bodies, sexualities, feelings and morals, in a temporary way, thus avoiding the physical and emotional responsibilities of the owner, characteristic of the net consumption.